Mengkaji Pengaruh Daya Tarik, Keahlian, Popularitas, dan Frekuensi Dukungan Influencer terhadap Sikap Konsumen pada Merek - Ayu, Putri; Hendrasto, Ferdian; Ariyani, Fitria (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The study aims to examine the influence of influencers' attractiveness, expertise, popularity, and frequency of endorsements on consumer attitudes toward brands. This study used a quantitative, survey-based approach, collecting data through questionnaires from 102 social media users in Malang City. Data were analyzed using multiple linear regression. The findings indicate that influencer expertise, popularity, and product quality perceptions significantly influence consumer attitudes toward brands. Meanwhile, influencer attractiveness and frequency of endorsements did not significantly influence consumer attitudes toward brands. The implication of these findings is the importance of companies selecting influencers with high expertise and strong popularity, as well as maintaining product quality perceptions to build positive consumer attitudes toward brands.